2019
DOI: 10.1186/s12864-019-6274-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of eight Lactobacillus buchneri strains isolated from food spoilage

Abstract: BackgroundLactobacillus buchneri is a lactic acid bacterium frequently associated with food bioprocessing and fermentation and has been found to be either beneficial or detrimental to industrial food processes depending on the application. The ability to metabolize lactic acid into acetic acid and 1,2-propandiol makes L. buchneri invaluable to the ensiling process, however, this metabolic activity leads to spoilage in other applications, and is especially damaging to the cucumber fermentation industry. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 68 publications
1
14
0
1
Order By: Relevance
“…The same phenomenon was observed in Lactobacillus buchneri strains. Nethery et al ( 57 ) suggested that the presence of self-targeting spacers indicates phage escape from immune attack by the CRISPR-Cas system during infection. Alternatively, Nobrega et al ( 58 ) proposed another interpretation that CRISPR-Cas systems accidentally acquire these spacers after these prophages have already been integrated into the bacterial hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenon was observed in Lactobacillus buchneri strains. Nethery et al ( 57 ) suggested that the presence of self-targeting spacers indicates phage escape from immune attack by the CRISPR-Cas system during infection. Alternatively, Nobrega et al ( 58 ) proposed another interpretation that CRISPR-Cas systems accidentally acquire these spacers after these prophages have already been integrated into the bacterial hosts.…”
Section: Discussionmentioning
confidence: 99%
“…WGS provides a comprehensive picture of all the genome content, allowing the identification of virulence, antibiotic resistance or probiotic/technological‐related determinants (Dong et al., 2019; Mannaa et al., 2019; Nethery et al., 2019; Rodrigo‐Torres et al., 2019; Tyson et al., 2018; Waseem et al., 2017). The quick and reliable identification of microbes responsible for foodborne outbreaks (Gerner‐Smidt et al., 2019) may lead to fast food recalls, contributing to prevent further health risks for the consumers.…”
Section: Characterization Of Lactic Acid Bacteria—identification and ...mentioning
confidence: 99%
“…Even though Ln. lactis genome is proportionally small; it has to maintain the capability of rapid and continuous evolution with its essential ecosystem via horizontal gene transfer of plasmids or transduction by phage infectivity [12][13][14]. Moreover, in order to maintain its viability and grow in a changing and highly specific ecosystem, LAB has to balance the maintenance of a strong immune system against bacteriophages, transmissible DNA elements, exogenous plasmids or transposases [14][15][16].…”
Section: Introductionmentioning
confidence: 99%